Upaya Peningkatan Pengetahuan Dan Kesadaran Mitigasi Banjir Melalui Program Sosialisasi Edukasi Masyarakat Di Desa Arosbaya - Rahmawati, Ifa; Hilya Agustin; Iftitah Nur Izzah; Elyza Wardana; Syifa Ghiffari (Public Administration Dept, Faculty of Social and Political Science, 2026)
Arosbaya is a coastal subdistrict located in Bangkalan Regency, Madura Island, East Java Province, which is prone to flooding. Flooding in Arosbaya Village has caused concern among residents; therefore, this outreach activity is expected to increase public knowledge and awareness of the importance of flood mitigation efforts. This study employs a mixed-methods research design, combining results from interviews and questionnaires using instruments such as observation sheets, interview sheets, and questionnaires. The results of descriptive statistical analysis across six aspects of knowledge indicate that the average level of knowledge among Arosbaya residents stands at 83.3%, which falls into the “good” category. Based on these data, the highest scores were found in the aspects of flood awareness and community cooperation, reaching 100% and 94.4%, respectively, reflecting the strength of social capital and the residents’ empirical experience. This study contributes to the development of a community-based education model for local disaster mitigation. From this activity, it is recommended that village residents collaborate on concrete actions such as community-based drainage repairs and routine community-based activities. Additionally, the involvement of the Bangkalan Regency Disaster Management Agency (BPBD) is essential to follow up on these proposed structural solutions.